EvoTech Industry Enterprise / Raden Luqman Haziq Raden Suzail ... [et al.] - Raden Suzail, Raden Luqman Haziq; Hamdan, Fadzlan Danish; Syakirin, Mohamad Syazwan; Mohd Rafique, Muhammad Muaz; Alias, Muhammad Aziq (2025)
EvoTech Industry Enterprise, based in Bayan Lepas Industrial Zone, Penang, Malaysia, specializes in creating innovative, multifunctional home appliances for modern lifestyles. Its flagship product, Dryon, is a hybrid device combining a hairdryer and a steam iron into a compact, energy-efficient solution. Designed for busy professionals, travelers, and urban residents, Dryon addresses the need for convenience, portability, and sustainability, aligning with EvoTech’s mission to simplify routines and enhance customer satisfaction. The company targets tech-savvy individuals aged 25-45 with mid-to-upper income levels across Southeast Asia. By leveraging digital platforms like Shopee and Lazada, alongside physical retail and influencer partnerships, EvoTech aims to establish a strong market presence. Financially, EvoTech projects RM9,043,200 in first-year revenue with 5-10% annual growth, supported by a detailed operational and marketing strategy. This business plan provides a roadmap for EvoTech’s growth and highlights its potential to revolutionize the home appliance market. By meeting consumer demands with innovative, eco-friendly solutions, EvoTech is well-positioned to secure investor support and become a trusted brand in the industry